AN ANALYSIS ILLOCUTIONARY ACT IN MUNIBA MAZARI’S “ WE ALL ARE PERFECTLY IMPERFECT” SPEECH - Bayuna Sofi; Widiarsih Mahanani (LINGUAMEDIA Journal, 2022)
Illocutionary act is an action that will be performed corresponding with utterance or the meaning understood by the listener. There are five types of illocutionary act that are: Representative, directive, commissive, declarative and expressive. This study aimed to find out the types of illocutionary acts and functions of five types in Muniba Mazari's speech. This study used Searle’s theory. The object of this study is Muniba’s speech. Then, this data were analyzed using the descriptive qualitative method. The result showed that the types of the illocutionary acts in Muniba’s speech consist of 55 representatives, 13 directives,14 expressive, 7 commisive and 6 declarative. The researcher also found the function of representative in muniba speech consists of stating, informing, describing, and complaining. Based on the research findings, Muniba presented various utterances that have to describe the function. She provided several descriptions of a situation that happened at that time, for example, to the audience. She also provided descriptions of situations or events that might happen in the and future. By performing these acts, Muniba expected the audience to better understand the information, opinion, and idea she presented in the speeches.